PENGARUH REWARD, PUNISHMENT TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Wasiati, Hera (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
This research aims to know whether reward and punishment affects employeesâperformance with work satisfaction as the intervening variable. The respondents were theeducation employees at STMIK AKAKOM with a total of 58 samples that used questionaires asthe data collecting method. descriptive and inferential analyses are used to analyze the dataand the hypothesis testing used t-statistic test, whereas RÂ² was used to evaluate how strong thefree variable altogether influences the bound variable.The results show that reward and punishment, both partially and altogether, positivelyand non significantly influence the employeesâ satisfaction. Reward and employeesâ satisfactionpartially and non significantly influence the employeesâ performance. Reward and punishmentas well as job satisfaction, on the other hand, altogether positively influence the employeesâperformance at work. In conclusion, all of the hypotheses proposed in this research areaccepted.Keywords: reward, punishment, job satisfaction, performance